THE INFLUENCE OF SOCIAL MEDIA MARKETING ACTIVITIES ON BRAND TRUST, BRAND EQUITY AND BRAND LOYALTY (Case Study On Instagram Shopee Indonesia) - Mentari Cahya Lestari; Osa Omar Sharif (SEAN Institute, 2023)
In Indonesia, the e-commerce industry is expanding fairly quickly. Social networking is now being used by several e-commerce businesses in Indonesia as a marketing technique. Indonesia's Shopee is one of them. Shopee, one of Indonesia's biggest online marketplaces, has more users than all of its rivals combined. Shopee uses Instagram, one of the social media platforms, to maintain contact with its customers. Shopee can use Instagram to develop and boost brand loyalty, brand equity and trust. This study attempts to ascertain whether Shopee's social media marketing initiatives on Instagram have a favorable impact on brand equity, brand loyalty, and brand trust. Quantitative techniques are used in this study. 385 respondents made up the study's sample. Descriptive analysis and structural equation modeling (SEM) are the analysis methods used. The SmartPLS software was used for the tests in this study. It is possible to draw the conclusion that social media marketing activities have a favorable and considerable impact on brand trust, brand equity and brand loyalty based on the findings of the data analysis that has been gathered. Additionally, brand equity and brand loyalty are positively and significantly impacted by brand trust. characteristics such as brand equity and also have a favorable and significant impact on brand loyalty.